(untitled) (Journal of Information Technologies in Education (ITE), 2012)
Actuality of the research presented in the article is confirmed by possibility of implementation of the tasks of Conception of introduction of media education in Ukraine, at the use of development and modernizations of the in Conception of introduction of media education in Ukraine, at the use of development and modernization of the pedagogical system «School-Minor Academy of Sciences».